Separating Cognitive Development From Language Development in the Acquisition of Negation Using International Adoption. - McDermott-Hinman, Annika; Zimmerman, Samuel; Snedeker, Jesse; Feiman, Roman (Journal of Experimental Psychology. General, 2026)
Children learning words face at least one challenge, maybe two. First, children must gather enough information to identify which concept maps to which word (a linguistic bottleneck). Second, for this mapping to be possible, children may need to acquire the concept itself if it is not already available (a conceptual bottleneck). We investigate whether children face both challenges or only the first when learning the English words for negation, a concept that is abstract and nonreferential, yet universal across human thought and languages. We tested whether a linguistic bottleneck is sufficient to explain how children learn to express negation by comparing negation production in typical English learners and older internationally adopted preschoolers, who are more conceptually mature but face a similar language-learning task. If infants normally face a conceptual bottleneck, older adoptees, who do not, should learn negation faster. If the only bottleneck is linguistic, the two groups should learn negation at the same rate relative to their acquisition of English. In Study 1, parent reports on the Communicative Development Inventory showed that older international adoptees and language-matched infant first-language learners begin producing no and not at the same point in vocabulary growth. Study 2 examined children's production of logical denial uses of negation words in longitudinal corpora of parent–child interactions. Adopted preschoolers' and language-matched infants' production of denials increased at the same rate relative to the mean length of children's utterances. Matching patterns of negation acquisition in internationally adopted preschoolers and first-language-learning infants support a solely linguistic, not conceptual, bottleneck on learning negation words. Public Significance Statement: Children face two possible challenges when learning word meanings: They need to learn which words express which concepts, and in some cases, they may need to learn the concepts themselves. Using negation ("no," "not") as a case study, we tested whether how hard it is for children to learn reflects a conceptual bottleneck (learning the concept of negation) or a linguistic bottleneck (learning how English expresses it). We compared infants learning English from birth with older internationally adopted preschoolers, who are more cognitively mature but have to learn English similarly to how first-language learners do. We found that older adoptees' greater conceptual maturity did not give them an advantage in learning negation: Both groups began using "no" and "not" to mean logical negation at similar points in language development. These results suggest that children's early challenge is primarily about learning which word expresses negation, not the underlying logical concept.